HUBUNGAN STRES PSIKOLOGIS DENGAN KADAR GULA DARAH SEWAKTU PADA PENDERITA DIABETES MELITUS TIPE II DI WILAYAH KERJA PUSKESMAS TAMANGAPA - Juhelnita Bubun; Sardi Anto; Anggi Melani Putri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Background: Maintaining the stability of random blood glucose levels in Type II Diabetes Mellitus (T2DM) patients remains a significant challenge in healthcare, particularly at the primary level. Various psychological stressors experienced by patients can affect their consistency in undergoing treatment, thus requiring attention as part of holistic condition management. Objective: This study aimed to determine the correlation between psychological stress and Random Blood Glucose (RBG) levels in Type II Diabetes Mellitus patients in the working area of Tamangapa Community Health Center (Puskesmas). Method: The research used a quantitative design with a cross-sectional approach. The study population included all T2DM patients registered from October to December 2024, with the sample determined using the total sampling technique. Psychological stress was measured using the DDS-17 questionnaire, categorized on an ordinal scale, while RBG levels were measured using a glucometer and stated in mg/dL on a numerical scale. Data analysis was performed using the Spearman statistical test. Results: There was a significant correlation between psychological stress and random blood glucose levels in T2DM patients p=0.031 (p<0.05). The direction of the correlation showed that the higher the level of psychological stress, the higher the random blood glucose levels.  Conclusion: There is a correlation between psychological stress and random blood glucose levels in T2DM patients in the working area of Tamangapa Community Health Center (Puskesmas). Psychological stress management is an integral part of healthcare services, and nursing care for diabetes patients helps to improve blood glucose control.